Arterial–Ventricular Coupling with Aging and Disease - Chantler, Paul D.; Lakatta, Edward (Frontiers in Physiology, 2012)
Age is the dominant risk factor for cardiovascular diseases. Understanding the coupling between the left ventricle (LV) and arterial system, termed arterial-ventricular coupling (EA/ELV), provides important mechanistic insights into the complex cardiovascular system and its changes with aging in the absence and presence of disease. EA/ELV can be indexed by the ratio of effective arterial elastance (EA; a measure of the net arterial load exerted on the left ventricle) to left ventricular end-systolic elastance (ELV; a load-independent measure of left ventricular chamber performance). At rest, in healthy individuals, EA/ELV is maintained within a narrow range, which allows the cardiovascular system to optimize energetic efficiency at the expense of mechanical efficacy. The age-associated alterations to arterial structure and function, including diameter, wall thickness, wall stiffness, and endothelial dysfunction, contribute to a gradual increase in resting EA with age. Remarkably there is a corresponding increase in resting ELV with age due to alterations to LV remodeling (loss in myocyte number, increased collagen) and function. During dynamic exercise there is an acute mismatch between the arterial and ventricular systems due to a disproportionate increase in ELV (approximately 200%) compared to EA (approximately 40%), to ensure that sufficient cardiac performance is achieved to meet the increased energetic requirements of the body. As a result EA/ELV decreases from an average of 0.58 to 0.34, and 0.52 to 0.27 in men and women, respectively. However, with advancing age the reduction in EA/ELV to acute maximal exercise is blunted, due to a blunted ELV. In this review, we provide an overview of the concept of EA/ELV, and examine the effects of age in the absence and presence of disease on EA/ELV and its functional consequences, and potential therapeutic interventions.